Evaluating the effectiveness of integrated traditional Chinese and Western treatment based on symptom grading: a study protocol for a multi-center, randomized controlled trial of patients with depressive disorder - Mai, Jiaxi; Zhou, Tingwei; Wang, Chen; Ye, Junrong; Chen, Jiao; Wang, Wen; Pan, Yuanxin; Wei, Yanheng; Yuan, Lexin; Yang, Hang; Wu, Shengwei; Guo, Jianxiong; et al. (Frontiers in Psychiatry, 2025)
BackgroundApproximately one-third of depressed individuals receive treatment globally. The application rate of traditional Chinese medicine (TCM) for treating depression globally remains relatively low. The proposed study presents a pilot trial to evaluate the effectiveness of interventions at different levels in improving depression status in community populations.MethodsA randomized controlled trial will be conducted in two communities in Guangdong, China, with a follow-up period of 12 weeks. Participants will be randomly allocated to control or intervention groups. Participants in the control group will be assigned to routine care, while participants in the intervention group will receive TCM intervention measures. The participants in the intervention group will receive integrated traditional Chinese and Western treatment according to the symptom grading of depression severity. Primary outcome measurements include the Patient Health Questionnaire (PHQ-9), the Hamilton Depression Rating Scale (HAMD-17), and the Self-Rating Depression Scale (SDS). Secondary outcome measurements include the Athens Insomnia Scale (AIS), the Epworth Sleepiness Scale (ESS), the Multiple Mental Health Literacy Scale (MMHL), the Short-Form 12 (SF-12), and the Treatment Emergent Symptom Scale (TESS). The data will be collected at baseline (T1), 2 weeks after intervention (T2), 4 weeks after intervention (T3), 8 weeks after intervention (T4), and 12 weeks after intervention (T5).DiscussionThis study will provide an experimental basis for the effectiveness of hierarchical integrated traditional Chinese and Western medicine (ITCWM) in improving the condition of patients with different degrees of depression. At the end of the study, it is expected for the experimental group to have an improvement in depressive symptoms and sleep quality and an enhancement in mental health awareness.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2300075169.